Immune responses to Streptococcus agalactiae in red tilapia, Oreochromis spp. following vaccination with non-adjuvanted and adjuvanted vaccine incorporated feed pellets - Nawi, Mohd Firdaus (2011)
Streptococcosis is an important bacterial disease in tilapia in many countries, including Malaysia. The two common Streptococcus species causing the disease are S. aga/actiae and S. iniae. In Malaysia, outbreaks of streptococcosis in red tilapia (Oreochromis spp.) were due to Streptoccoccus aga/actiae while infection by Streptococcus iniae has never been reported. Mass mortalities among red tilapia in cage-culture system were reported to occur usually during the dry months of the year, between April and August when water temperature was high.This study was conducted to investigate the effect of high water temperature on the susceptibility of red tilapia to infection by Streptococcus aga/actiae, the immune response by red tilapia following exposure to live S. aga/actiae and the protection following vaccination against streptococcosis. To achieve the first objective, eight groups of red tilapias of approximately 100 g were infected intraperitoneally with 0.5 mL of live S. aga/actiae at 6.3 x 106 CFU/mL, 6.3 x 107 CFU/mL, 6.3 x 108 CFU/mL and 6.3 x 109 CFU/mL. Four groups were kept at normal water temperature of 27°C ± 2°C while the rest were kept in high water temperature of 33°C± 2°C for a period of one week. The high water temperature caused an increased in the susceptibility of red .tilapia to S. aga/actiae infection as indicated by the rapid rate of mortality at lethal dose 50 (L050). The period to achieve 100% mortality in the high temperature group was faster than the normal water temperature group, in four days compared to seven days. The lethal dose 50 (L050) for groups that were kept in high water temperature was 5.68 x 106 CFU/mL, significantly (p<0.05) lower than those that were kept in normal water temperature (2.29x107 CFU/mL). The clinical signs included loss of appetite, lethargy, unilateral or bilateral exophthalmia, cloudy eyes, erratic swimming and inflammation of the skin. Once the susceptibility was determined, formalin killed whole-cell S. aga/actiae at the concentration of 6.7 x 106 CFU/mL was incorporated homogenously into fish pellet as feed vaccine (FNV vaccine). The vaccine was then administered orally to the red tilapia in three different vaccination - regimes; once (F10), thrice (F30) and five times a week (F50). Body mucus and blood serum were sampled every week for eight weeks to analyze the mucosal and systemic antibody responses by using ELISA. Immunization by FNV vaccine resulted in significant (p<O.05) increase in the serum and mucus antibody levels (lgM) as early as week 2 in all vaccinated groups, while the control unvaccinated group (Fe) showed insignificant (p>O.05) increase of the serum and mucus antibody levels. Group F5D showed the highest antibody levels, followed by groups F3D and F1D. At the end of the experiment, twenty fishes from each group were challenged by immersion while another twenty were challenged intra-peritoneal. Survival rate was low indicating poor protective immune response in all groups of tilapia tested. Gut samples were obtained at the end of the experiment and subjected to . histological analyses to examine the presence of gut-associated lymphoid tissue (GALT). According to the analyses, exposure at the rate of once a week to FNV vaccine was sufficient to stimulate GALT and skin mucus antibody responses. However, more frequent exposures stimulated better responses by GALT as observed in red tilapias of groups F3D and F5D. As expected, unvaccinated red tilapias failed to stimulate any GALT development. In conclusion, vaccination using FNV vaccine stimulated mucosal and systemic immunities but the protection provided was unsatisfactory. Following the episode of poor protection provided by oral administration of FNV vaccine, the vaccine was further modified by adding Freund's Incomplete Adjuvant (FIA) into the vaccine, a known potent immune response enhancer at both humoral and cellular levels. The feed adjuvanted vaccine (FAV) was found to improve the mucosal immune response a·~d elicited excellent systemic immune response. Apart from higher body mucus,both gut lavage fluid and blood serum antibody titers were also higher than the FNV vaccine. The FAV vaccine also provided 100% protection following challenged with 3.4 x 109 CFU/mL of live S. aga/actiae, significantly (p ~ 0.05) higher than protection provided by FNV vaccine. Similarly, the size of GALT and the number of lymphocytes in the FAV-vaccinated group were significantly (p<0.05) greater compared to the FNV-vaccinated group. In conclusion, this study demonstrated that adjuvanted vaccine (FAV) was more effective compared to the non-adjuvanted vaccine (FNV). The FAV vaccine effectively stimulated both mucosal and systemic immunity and . enhanced protection against S. aga/actiae infection in red tilapia. Therefore, FAV vaccine is the best candidate for control of streptococcosis in red tilapia.